Tutorials for introduction to engineering materials - Merion Media Inc. ([S.l.] : Merion Media Inc., 1998)
Disc 1 covers the topic of corrosion protection, mechnical behaviour, materials structures, dislocation and plastic flow, annealing, metal fatigue, phase diagrams and carbon steel. Disc 2 explains about hard materials, precipitation hardening, bicycle construction, polymers, composites, magnetic materials and electronic materials
Keywords: Materials; Engineering -- Study and teaching